2007
DOI: 10.1681/asn.2007020221
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Frailty among Dialysis Patients

Abstract: The construct of frailty has been associated with adverse outcomes among elderly individuals, but the prevalence and significance of frailty among patients with end-stage renal disease have not been established. The aim of the current study was to determine the prevalence and predictors of frailty among a cohort of incident dialysis patients and to determine the degree to which frailty was associated with death and hospitalization. We studied a cohort of 2275 adults who participated in the Dialysis Morbidity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
586
8
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 570 publications
(656 citation statements)
references
References 15 publications
30
586
8
18
Order By: Relevance
“…The data showed an inverse relationship between the prevalence rates for frailty and the level of renal function, and dialysis patients have been shown to experience one of the highest prevalence rates for frailty in any single population. In the Dialysis Morbidity and Mortality Study (DMMS) Wave II study, a total of 67.7% of patients of all ages met collective criteria for frailty (14). While the prevalence was maximal in the oldest age category (78.8% of those who were older than 80 yr were considered frail), a significant number of younger individuals fulfilled criteria for frailty (66.4% of those aged 50 to 60 yr).…”
Section: Frailtymentioning
confidence: 99%
“…The data showed an inverse relationship between the prevalence rates for frailty and the level of renal function, and dialysis patients have been shown to experience one of the highest prevalence rates for frailty in any single population. In the Dialysis Morbidity and Mortality Study (DMMS) Wave II study, a total of 67.7% of patients of all ages met collective criteria for frailty (14). While the prevalence was maximal in the oldest age category (78.8% of those who were older than 80 yr were considered frail), a significant number of younger individuals fulfilled criteria for frailty (66.4% of those aged 50 to 60 yr).…”
Section: Frailtymentioning
confidence: 99%
“…The mean age 6 standard deviation of the cohort was 57 6 10 years. Sixty-three percent of the cohort were men, with a median MELD score of 17 (interquartile range [13][14][15][16][17][18][19][20][21]. Alcohol was the most common cause of cirrhosis (44%).…”
Section: Patient and Admission Characteristicsmentioning
confidence: 99%
“…(8)(9)(10) One of these is its inability to account for an individual's performance status. Performance status and the linked concept of frailty are known robust predictors of adverse outcomes in diverse populations (11)(12)(13)(14)(15)(16)(17) including cirrhosis, (18)(19)(20)(21) often outperforming traditional prognostic markers. (22,23) Developed in 1948, the Karnofsky Performance Status (KPS) is one of the oldest performance status scales.…”
mentioning
confidence: 99%
“…Johansen et al reported a higher rate of frailty in older patients with ESRD (age , 40 years, 44.4%; age 60-70 years, 74.2%; age .80 years, 78.8%) (4). For those with frailty, after 1 year adjusted HRs were 2.24 (95% CI, 1.60-3.15) for mortality and 1.56 (95% CI, 1.36-1.79) for hospitalization (4).…”
Section: Frailtymentioning
confidence: 99%